(untitled) (AYUSHDHARA, 2025)
Micturition or urination is a complex and multi system involved process. In the present era of varying lifestyle even the minimal alterations make a huge difference to the system and so the healthcare worker may encounter such cases during the routine practice. One among them is urinary incontinence where the symptoms are highly prevalent among women and the patient is unable to hold the urge to urinate voluntarily. As per Ayurveda, urinary disorders are classified as Mutra Apravritti and Atipravritti Rogas caused by the imbalance of Vata dosha, particularly Apana Vata, which governs the downward movement of metabolic waste including urine. This report presents the case of a 22-year-old female who experienced severe degree of symptoms with urgency and increased frequency of urination for 1 year. She also reported with associated complaints of abdominal pain. After the thorough examination, the patient was treated efficiently with the principles of Ayurveda as mentioned in the classic.